Gondhsorai Goss (Cinnamomum cecicodophne Meissn), Tong-Loti (Eupatorium Cannabinum L and Athia/Bhim Kol (Musa Paradisiacal L): Sacred plants of Sonowal Kachari Tribe of Assam, North East (Bhartiya Knowledge Systems, 2024)
The Sonowal Kachari tribes are one of the indigenous tribal people belonging to Schedule tribes community who practice different superstitions and cultural traditions. The paper represents three sacred plants which are used in various cultural festivals and also symbolize the use of plants to cure various diseases. Thus sacred plants signify the ethno-ecological knowledge system of  the indigenous communities.